Note on the rediscovery of Tigridia hintonii (Tigridieae: Iridaceae) in the state of Guerrero, Mexico - Munguía-Lino, Guadalupe; Castro-Castro, Arturo; Rodríguez, Aarón (Instituto de Ecología, A.C., 2015)
A new record of Tigridia hintonii (Iridaceae) in the state of Guerrero, Mexico, is documented. The species was first collected by George B. Hinton in Fresnos, District of Mina, Zirándaro, Guerrero in October 1936. Since then, other specimens of this taxon had not been collected until 2012. A complete morphological description and figures are provided. Additionally, data of distribution, habitat, conservation assessment and phenology are presented.